Coinfection of cytomegalovirus and strongyloidiasis presenting as massive gastrointestinal bleeding in an immunocompromised host: a case report - Huu, Thanh Nguyen; Thu, Hoai Mai; Quy, Khoa; Thanh, Mai Vo; Thi, Nga Dinh; Ngoc, Quang Pham Minh; Thi, Tuyet Duong; Canh, Binh Nguyen; Lam, Tung Nguyen; Doan, Ky Thai (Frontiers in Medicine, 2024)
Cytomegalovirus (CMV) infection is an opportunistic disease in immunocompromised patients that may appear without symptoms, with constitutional symptoms, or as a tissue-invasive disease. Strongyloides stercoralis infection often manifests with non-specific symptoms; however, it can lead to severe malabsorption and extraintestinal dissemination by accelerated autoinfection. The coinfection of CMV and Strongyloides stercoralis has rarely been reported, particularly with solely severe gastrointestinal bleeding. A 29-year-old female patient with a history of nephrotic syndrome treated with long-term corticosteroid and poorly controlled type 2 diabetes presented with a 20-day history of persistent epigastric pain, diarrhea, and significant weight loss. At the hospitalization, the patient appeared to have persistent gastrointestinal bleeding, leading to hypovolemic shock and diabetic ketoacidosis. Strongyloides stercoralis was detected by the duodenal biopsy results, and the polymerase chain reaction of these samples was positive for CMV. The patient underwent upper endoscopy four times to control the bleeding and was treated with ivermectin and ganciclovir. The patient improved gradually and was discharged after 23 days of hospitalization. The coinfection of CMV and Strongyloides stercoralis causing massive gastrointestinal (GI) bleeding has been rarely reported. To the best of our knowledge, this is also the first case of coinfection of these pathogens in an immunocompromised patient complicated with hypovolemic shock caused by GI bleeding and diabetic ketoacidosis. Clinicians should have a high index of suspicion and test simultaneously CMV and Strongyloides stercoralis in patients with immunosuppression, other risk factors, or unexplained gastrointestinal symptoms.